2007
DOI: 10.2353/ajpath.2007.070325
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II Co-Chaperone General Cell UNC-45 Overexpression Is Associated with Ovarian Cancer, Rapid Proliferation, and Motility

Abstract: Both tumor cell proliferation and metastasis are dependent on myosin II. Because UNC-45 is required to chaperone the assembly of a functional myosin II motor, we examined the expression of the general cell (GC) UNC-45 isoform in ovarian tumors. Serous carcinoma expressed elevated levels of GC UNC-45 compared with normal ovarian surface epithelium and benign cystadenoma. High-stage exhibited greater GC UNC-45 expression than low-stage serous carcinoma. Similarly, GC UNC-45 transcripts and protein levels were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(100 citation statements)
references
References 44 publications
11
89
0
Order By: Relevance
“…Recently, elevated UNC45A levels have been detected in serous ovarian carcinomas biopsies and UNC45A was found to affect cell proliferation and motility (12). Our data provide a second explanation for the increased UNC45A levels in cancer, as high UNC45A may provide a selective advantage to tumor cells by inhibition of RA-dependent proliferation arrest and differentiation.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Recently, elevated UNC45A levels have been detected in serous ovarian carcinomas biopsies and UNC45A was found to affect cell proliferation and motility (12). Our data provide a second explanation for the increased UNC45A levels in cancer, as high UNC45A may provide a selective advantage to tumor cells by inhibition of RA-dependent proliferation arrest and differentiation.…”
Section: Discussionsupporting
confidence: 56%
“…The expression of UNC45A protein in ovarian carcinoma is associated with tumor stage and grade (12). Malignant serous carcinoma expresses elevated levels of UNC45A compared with normal ovarian surface epithelium and benign cysts (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UNC-45a expression could not compensate for UNC-45b loss of function during heart development Immunohistochemistry of the wild-type and mutant hearts with monoclonal antibody to UNC-45A, a molecular chaperone for non-muscle myosin II involved in cell proliferation and migration Bazzaro et al, 2007;Guo et al, 2011), showed no differences in the UNC-45a protein accumulation of wild-type and the three mutant hearts (Fig. 7).…”
Section: Defective Cardiac Looping In Mutant Embryonic Heartsmentioning
confidence: 99%
“…UNC-45B was designated the Striated Muscle isoform (SM UNC-45) because its expression is restricted to heart and skeletal muscles. Knockdowns of UNC-45A lead to decreased proliferation of cultured myogenic and ovarian cancer cells, 20,21 whereas knockdowns of UNC-45B disrupt sarcomeric organization in cultured myoblasts and zebrafish. 20,22 Importantly, the elevated expression of the UNC-45A mRNA and protein is found in ovarian tumor samples and derived cell lines.…”
Section: Introductionmentioning
confidence: 97%